2016
DOI: 10.1073/pnas.1601872113
|View full text |Cite
|
Sign up to set email alerts
|

Humans are sensitive to attention control when predicting others’ actions

Abstract: Studies of social perception report acute human sensitivity to where another's attention is aimed. Here we ask whether humans are also sensitive to how the other's attention is deployed. Observers viewed videos of actors reaching to targets without knowing that those actors were sometimes choosing to reach to one of the targets (endogenous control) and sometimes being directed to reach to one of the targets (exogenous control). Experiments 1 and 2 showed that observers could respond more rapidly when actors ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 24 publications
(22 reference statements)
7
29
0
Order By: Relevance
“…By occluding large, non-overlapping sections of the Attacker's body, we replicated the previous finding that adults can use distributed information in the body for action prediction (Pesquita et al, 2016;Vaziri-Pashkam et al, 2017). Children were not able to use the distributed information in the body as efficiently as adults.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…By occluding large, non-overlapping sections of the Attacker's body, we replicated the previous finding that adults can use distributed information in the body for action prediction (Pesquita et al, 2016;Vaziri-Pashkam et al, 2017). Children were not able to use the distributed information in the body as efficiently as adults.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies have shown that adults predict the target of an action and make anticipatory eye movements to that location (Flanagan & Johansson, 2003). These predictions are likely based on kinematic cues (Cavallo et al, 2016;Diaz, Fajen, & Phillips, 2012) that are widely distributed across body of the actor (McMahon et al, 2019;Pesquita, Chapman, & Enns, 2016;Vaziri-Pashkam, Cormiea, & Nakayama, 2017). Adults can use this distributed information to make predictions even when the locus of the information is far from the body part performing the action.…”
Section: Action Prediction In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…If movement is the result of competition between internally represented choice options, then our movements broadcast our evolving decision process to the world. Others are able to pick up on these decision‐making signals simply by observing our movements and are able to use them to guide their own actions . This is a key aspect of body language, gesturing, and coordination, and might have been an important mechanism for the evolution of humans as a social species.…”
Section: Conclusion and Extensionsmentioning
confidence: 99%
“…Others are able to pick up on these decision-making signals simply by observing our movements and are able to use them to guide their own actions. 174,175 This is a key aspect of body language, gesturing, and coordination, and might have been an important mechanism for the evolution of humans as a social species.…”
Section: Conclusion and Extensionsmentioning
confidence: 99%